Barriers to Adoption of Mineralocorticoid Receptor Antagonists in Patients With Heart Failure: A Mixed‐Methods Study. Issue 3 (31st March 2016) - Dev, Sandesh; Hoffman, Trisha K.; Kavalieratos, Dio; Heidenreich, Paul; Wu, Wen‐Chih; Schwenke, Dawn C.; Tracy, Sarah J.
Abstract : Background: Mineralocorticoid receptor antagonists (MRAs) are the most underutilized pharmacotherapy for heart failure. Minimal data are available on the barriers to MRA adoption from the perspective of prescribing clinicians. Methods and Results: A mixed‐methods study consisting of a survey (n=50), focus groups (n=39), interviews (n=6) with clinicians at a single US Department of Veterans Affairs medical center served to ascertain barriers to optimal use of MRAs. Participants were drawn from 6 groups: cardiology providers, cardiology fellows, hospitalists, clinical pharmacists, internal medicine residents, and primary care providers. Qualitative data were iteratively coded with qualitative data analysis software. The survey response rate was 17.3%. Overall, 51% of survey respondents were unfamiliar with eplerenone, and 6% were unfamiliar with spironolactone. In addition, 30% of respondents reported that they would order a laboratory test >2 weeks after a new MRA prescription, although that is beyond the guideline recommendation. Most providers correctly identified New York Heart Association class 3 and 4 patients as MRA eligible, but only 42% identified class 2 patients as MRA eligible. Through analysis of focus groups, we identified 8 barriers to MRA use in 3 categories: patient‐based barriers (concerns about polypharmacy and comorbidities, adverse effects, perceived patient nonadherence), provider‐based barriers (unclear roles and responsibilities, coordination and transitions of care, lack of experience or familiarity with MRAs), and system‐based barriers (system overload and provider time constraints, lack of systematic follow‐up procedures). Conclusions: Eight primary barriers to MRA adoption at the provider, patient, and health system levels were identified from the prescriber perspective. These barriers can inform the creation of multilevel interventions that will be required to close the gap in MRA adoption.